238 Transcriptome profiling of primary bovine macrophages from cows with Johne's disease suggests a tolerance state induced by convergent signalling via NF-κB and its synergistic tolerized genes. (7th December 2018) - Bissonnette, N; Gendron, D; Ariel, O; Dudemaine, P; Ibeagha-Awemu, E
Abstract: Mycobacterium avium ssp . paratuberculosis (MAP) causes Johne's disease (JD) in ruminants. The mechanisms of JD pathogenesis are still unclear, but it is known that this obligatory bacterium manipulates macrophages for its survival and long-term infection success in its host. A comparative transcriptomic analysis (next-generation RNA sequencing) was performed to study the global transcriptional shift mechanism observed in macrophages from JD-positive (+) cows (serum-ELISA positive for MAP antigens and excreting live MAP in their feces). Six JD-negative (−) cows and six JD(+) cows were selected. Monocyte-derived macrophages (MDM) were infected ex vivo for 1, 4, 8, and 24 h with live MAP at a multiplicity of infection of 10:1. While MAP-infected macrophages from JD(−) cows showed a robust pro-inflammatory induction of 3, 765 genes ( p < 0. 05) during the first 1 to 8 h (TNF, NF-κB, and cytokine members), only 31 genes were differentially expressed for JD(+). The top upregulated genes subsequently (24 h) shifted toward an anti-inflammatory and pro-resolution state. This distinct tolerization signature was confirmed in JD(+) macrophages during a subsequent exposure to MAP. Validation of key tolerized genes showed that JD(+) macrophages were shaped to not respond to subsequent transcriptional and immune MAP stimuli. For instance, while a synergistic activation of NF-κB, MAPK, and IRF pathways were associated with acute cytokine responses in JD(−), the canonical NF-κB pathway (p50/p65/BCL3) and the sequestosome were tightly regulated in JD(+) macrophages. Understanding the precise mechanism of the distinct transcriptional stimulation observed in JD(+) macrophages is paramount for eventual development of a treatment or even treatments. Our findings support the hypothesis that MAP could induce a tolerant state in the circulating monocytes of JD(+) cows, thus preventing response to a subsequent MAP exposure. This report provides important clues about MAP survival mechanisms and how MAP manipulates macrophages to promote disease persistence in dairy cattle.